Perbedaan Motivasi Belajar, Mutu Keterampilan Belajar, dan Self Regulated Learning Siswa Kelas Diklat dan Siswa Kelas Reguler - Hidayat, Hafiz; Nirwana, Hernan; Syahniar, Syahniar (Universitas Negeri Padang, 2016)
This research was conducted as there was a difference between learning achievement of the students in regular class and in training class. Learning motivation, learning skill quality and self regulated learning are factors assumed to affect the students’ learning achievement. This research was intended to: (1) reveal the difference between learning motivation of the students in regular class and in training class, (2) the difference between learning skill quality of the students in regular class and in training class, and (3) self regulated learning of the students in regular class and in training class.This research applied descriptive comparative method. The population of the research was 312 students in class XI of SMA N 5 Padang. By using purposive sampling technique and simple random sampling technique, 65 students were chosen as the sample. The instrument of the research were learning motivation questionnaire (the reliability was 0.950), self regulated learning questionnaire (the reliability was 0.817), and AUM PTSDL Format SLTA (the reliability was 0.76). The data gathered then were analyzed by using Multivariate Analysis of Variance (MANOVA).The research findings indicated that: (1) learning motivation of the students both in training class and in regular class at SMA N 5 Padang was in high category, (2) in which significant difference learning motivation of the students in regular class was higher than that of students in training class, (3) the quality of students' learning skills training classes as very bad and regular classroom students classified as not good at SMA N 5 Padang, (4) there was a significant difference between learning skill quality of the students in regular class and in training class in which learning skill quality of the regular class was higher than that of the students in training class, and (5) students self regulated learning training class and regular class in high at SMA N 5 Padang is category good, (6) there were no significant differences in which self regulated learning training class students together with students regular class, (7) there are significant differences between the motivation to learn, the quality of learning skills, and self regulated learning training class students and students' regular classroom.